Synthesis of Substituted 5-Phenyltriazolylquinazolinylamino Nicotinic Acid Esters, Screened their Antibacterial Activity and Molecular Docking Studies - Mood, Shilpa; Boda, Uma; Guguloth, Hanmanthu (Asian Journal of Chemistry, 2022)
Quinazolines and imidazoles are substantial attention because of the several varieties of their biological activities. Substituted 5-phenyl-[1,2,4]triazolo[4,3-c]quinazolin-3-yl)amino)nicotinates were synthesized from anthranilamide as starting material by cyclization with benzaldehyde gave 2-phenyl-2,3-dihydroquinazolin-4(1H)-one, then followed by treated with Lawesson’s reagent and hydrazine hydrate to produce hydrazine by replaced the sulfur atom. 5-Phenyl-[1,2,4]triazolo[4,3- c]quinazolin-3-amine obtained by cyclization of hydrazine compound with cyanogen bromide, followed by amidation with substituted 6-fluoronicotinates in the presence of DIPEA in DMSO solvent to get corresponding the title compounds. These compounds further evaluated for their in vitro antibacterial activity studies and molecular docking studies. Some of the newly synthesized compounds were found to possess excellent growth inhibition activity compared to commercial standards drugs like penicillin-G and streptomycin. All the synthesized compounds were confirmed by their elemental analysis, infrared, 1H, 13C NMR and mass spectral data.